A CULTURE OF TOLERANCE IN ISLAMIC RELIGIOUS THEORETICAL SOURCES - Abdullayev Akmal Nasriddinovich (Galaxy International Interdisciplinary Research Journal, 2022)
Since the early days of independence, the creation of wide opportunities for the land of representatives of various religious confessions operating in Uzbekistan is the result of a rational policy carried out by our state in the process of building a democratic society. The First President Of The Republic Of UzbekistanA.As Karimov noted:”from the first days of our independence, the restoration of an enormous, invaluable spiritual and cultural heritage created by our ancestors for many centuries has become an incredibly important task, which has risen to the level of state policy".[1] the most effective way to achieve a culture of tolerance in the independent Uzbekistan is to follow the Constitution and the law “on the land of conscience and religious organizations”. Article 18 of the Constitution of the Republic of Uzbekistan states:”all citizens of the Republic of Uzbekistan have the same rights and freedoms and are equal before the law, regardless of gender, race, nationality, language, religion, social status". [2] in fact, all the laws that are being adopted are in the interests of man, for their future.